2016
DOI: 10.1177/0269216316634246
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive report of end-of-life care practices occurring in two neonatal intensive care units

Abstract: Variability exists in end-of-life care practices such as provision of analgesic and sedative medications. Other practices such as discontinuation of cardiorespiratory monitors and use of parent rooms are more uniform. More research is needed to understand variation in neonatal end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
3
31
1
1
Order By: Relevance
“…This study demonstrated major differences in mortality, age at death, cause of death and end‐of‐life decisions in full‐term neonates admitted to the NICU and PICU at the same children's hospital in the Netherlands. Our study confirmed that most of the deaths in the NICU were as a result of perinatal asphyxia , which often leads to circulatory insufficiency and secondary cerebral and pulmonary dysfunction. After asphyxia, noncardiac congenital malformations were also common in the NICU.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study demonstrated major differences in mortality, age at death, cause of death and end‐of‐life decisions in full‐term neonates admitted to the NICU and PICU at the same children's hospital in the Netherlands. Our study confirmed that most of the deaths in the NICU were as a result of perinatal asphyxia , which often leads to circulatory insufficiency and secondary cerebral and pulmonary dysfunction. After asphyxia, noncardiac congenital malformations were also common in the NICU.…”
Section: Discussionsupporting
confidence: 82%
“…Most of the studies on neonatal deaths in the Western world have focused on preterm infants and have identified four major causes of mortality: prematurity, congenital malformations, perinatal asphyxia, and sepsis . In the Netherlands, full‐term neonates who suffer from critical illnesses are commonly admitted to a neonatal intensive care unit (NICU) or paediatric intensive care unit (PICU) depending on the nature of their illness .…”
Section: Introductionmentioning
confidence: 99%
“…Upon diagnosis, in light of the prognosis, the family elected for comfort care, and the patient expired that day. Time to death after withdrawal of life-sustaining treatment is not commonly a protracted event(17, 18). The Delphi panel could not achieve consensus with respect to earlier election of palliative care if the diagnosis had been known soon after birth.…”
Section: Impact Of Rwgs-associated Precision Medicine On Healthcare Umentioning
confidence: 99%
“…Despite advances in medical treatments, not all newborns survive: there is a 3.1‰ perinatal mortality rate and a 1.8‰ neonatal mortality rate (4) which corresponds to the death of 1 out of 476 children under one month of age. More than 90% of those deaths occur in NICU, after complex decisions and dilemmas to withdraw or to withhold life-sustaining treatments; this brings enormous challenges to highly differentiated teams (5)(6)(7) . Neonatal mortality data put us on the list of countries with the lowest mortality rate among children who are less than 28 days of age.…”
Section: Introductionmentioning
confidence: 99%
“…They may, at an early stage, be applied in addition to curative care and be more evident when the curative objective is no longer appropriate and the intention is to prevent and relieve newborns' suffering and the pain endured by families and increase their quality of life while they are still alive and as they face imminent death (7)(8)(9)(10)(11) . In the case of newborns who are close to death, the objective is to help them have a "good death", always maintaining a deep respect for human dignity (1,6,12) . The NPC can be coupled with intensive care at any stage of the disease in order to provide care to newborns and their families in a constant, comprehensive and individualized way and will also have clear benefits for health professionals (12) .…”
Section: Introductionmentioning
confidence: 99%